1999
DOI: 10.1088/0022-3727/32/3/018
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic spin resonance in hydrogen-charged stainless austenitic steel

Abstract: Hydrogen-charged stainless austenitic steel Cr18Mn20 alloyed with 0.88 mass% of nitrogen is studied using a magnetic spin resonance method. The steel is paramagnetic before as well as after hydrogen charging, which allows one to observe electron spin resonance (ESR). It is shown that hydrogen causes a significant increase of the signal from conduction electrons in the ESR spectrum (CESR), i.e., it increases the concentration of free electrons in the alloy. Hydrogen charging results also in a stronger exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…This result is consistent with the experimental data obtained using conduction electron spin resonance [10][11][12][13]). According to data in Fig.…”
Section: Atomic Interactionssupporting
confidence: 92%
“…This result is consistent with the experimental data obtained using conduction electron spin resonance [10][11][12][13]). According to data in Fig.…”
Section: Atomic Interactionssupporting
confidence: 92%
“…Mössbauer measurements of the hydrogen effect on the probability of the absorption of y-quanta in austenitic steels have shown that hydrogen increases the Debye temperature (Gavriljuk and Shivanyuk 1999), i.e. Mössbauer measurements of the hydrogen effect on the probability of the absorption of y-quanta in austenitic steels have shown that hydrogen increases the Debye temperature (Gavriljuk and Shivanyuk 1999), i.e.…”
Section: Hydrogen Embrittlementmentioning
confidence: 99%
“…One can see that the iodine increases the concentration of free electrons in the austenitic steels in consistency with the increase in the density of electron states at the Fermi level of the fcc iron, as presented in Figure 1. Using the same experimental technique, we have shown earlier that hydrogen also increases the concentration of free electrons in the austenitic steels [30,46]. …”
mentioning
confidence: 83%
“…A piece of the MgO: Cr 3+ compound with the number of spins 1.1⋅10 16 served as a reference sample. The analysis of the experimental spectra has been carried out based on the theory of ESR for free electrons [44] and using a technique developed in our previous studies [45,46]. Measurements of the amplitude-dependent internal friction for studies of dislocation properties were carried out within the strain amplitude of 0.5⋅10 -6 to 5⋅10 -4 using an automated inverted pendulum operating at temperatures from 80 to 580 K and frequencies of about 1 Hz.…”
Section: Coefficient K = 10mentioning
confidence: 99%